Does the Stock Market React to Unsolicited Ratings? - Patrick Behr; André Güttler (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2006)
This paper investigates whether the stock market reacts to unsolicited ratings for a sample of S&P rated firms from January 1996 to December 2005. We first analyze the stock market reaction associated with the assignment of an initial unsolicited rating. We find evidence that this reaction is negative and particularly accentuated for Japanese firms. A comparison between S&P's initial unsolicited ratings with previously published ratings of two Japanese rating agencies for a Japanese subsample shows that ratings assigned by S&P are systematically worse. Further, we find that the stock market does not react to the transition from an unsolicited to a solicited rating. Comparison of the upgrades in the sample with a matched-sample of upgrades of solicited ratings reveals that the price reactions are no different. In addition, abnormal returns are worse for firms whose rating remained unchanged after the solicitation compared to those for upgraded firms. Finally, we find that Japanese firms are less likely to receive an upgrade. Our findings suggest that unsolicited ratings are biased downwards, that the capital market therefore expects upgrades of formerly unsolicited ratings and punishes firms whose ratings remain unchanged. All these effects seem to be more pronounced for Japanese firms.
Keywords: G23; G14; 330